Strengthening the Moderate Character of Students’ through the Co-curricular Islamic Education Tutorial Program at Public Universities - Mokh. Iman Firmansyah; Encep Syarief Nurdin; Kama Abdul Hakam; Aceng Kosasih; Ahmad Hakam (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
This study aims to investigate the Co-curricular role of the Islamic Education (PAI) Tutorial Program in strengthening the moderate character of students at public universities from the perspective of Emile Durkheim's collective social theory. A qualitative approach and case study method were chosen to investigate information from participants through documentation, interviews and observation. The data were analyzed through the stages of reduction, display, and drawing conclusions. The results of the study found that within a collective social framework, the PAI Tutorial Program policy is part of social responsibility that is rolled out rationally and strategically as a control effort carried out by the university by considering facts of religious understanding and behavior, as well as the phenomenon of radicalism. To strengthen the moderate character of students, this program is carried out consistently in objectives, materials, and activity units so as to support social functions through explanation and sharing of religious knowledge, role models, discipline, attitudes and open views, mutual respect and appreciation for differences of opinion, the attitude of accepting or rejecting views is based on strong arguments, and the strengthening of adab in the era of globalization. Meanwhile, to strengthen these social responsibilities and functions, this program fulfills two moral elements, namely being binding with the application of strict discipline. Keywords: Moderat Character, Co-curricular, Strengthening the Moderate Character